Kepemilikan Institusional sebagai Pemoderasi Pengaruh Perencanaan Pajak dan Profitabilitas pada Manajemen Laba - Wirawan, I Made Dwi Sumba (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p03, 2020)
This study examines the effect of tax planning and profitability on earnings management. In addition, this study also examines the ability of institutional ownership as a moderating variable. The number of samples analyzed was 75 samples of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (BEI) for five years. The sampling method was nonprobability with a purposive sampling technique. The analysis technique used is multiple linear regression and Moderated Regression Analysis (MRA). The results of the analysis show that tax planning has a positive effect on earnings management. However, profitability has no effect on earnings management. Institutional ownership weakens tax planning in earnings management. However, institutional ownership does not moderate the effect of profitability on earnings management. Keywords: Tax Planing; Profitability; Earning Management; Institusional Ownership.